Keindahan Iluminasi dan Kaligrafi Dalam Manuskrip Mushaf Hj. Fatimah Siti Hartinah Soeharto - Amnah Nur Izzah; John Supriyanto; Sulaiman M. Nur (Program Magister Ilmu Al-Qur'an dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2022)
This article aims to determine the decorative and visual forms contained in the Mushaf Hj. Fatimah Siti Hartinah Suharto initiated by Suharto's family to commemorate the death of Tien Suharto's mother. By using the philological method, it can be concluded that Mushaf Hj. Fatimah Siti Hartinah Suharto contains relevance to the development of the Qur'anic manuscripts in Indonesia. This is because Mushaf Hj. Fatimah Siti Hartinah Suharto is the first manuscript in Indonesia made in the name of a woman. This manuscript is also a sign that Indonesia has a high Islamic value. The process of making Mushaf Hj. Fatimah Siti Hartinah Suharto is being watched closely, in an effort to maintain the authenticity of the Qur’an so that there are no errors in writing. The relevance of Mushaf Hj. Fatimah Siti Hartinah Suharto in the development of manuscripts with illuminated calligraphy shows that art, culture and religion can coexist when presented correctly.